Impact of Adjuvant Use of Midodrine to Intravenous Vasopressors: A Systematic Review and Meta-Analysis. (17th May 2021) - Al-Abdouh, Ahmad; Haddadin, Sadam; Matta, Atul; Jabri, Ahmad; Barbarawi, Mahmoud; Abusnina, Waiel; Radideh, Qais; Mhanna, Mohammed; Suffredini, Dante A.; Michos, Erin D.
Abstract : Purpose . To evaluate the efficacy and safety of midodrine use in intensive care units (ICU) to facilitate weaning off intravenous vasopressors (IVV). Methods . We searched PubMed/MEDLINE, Cochrane library, and Google Scholar (inception through October 18 th, 2020) for studies evaluating adjuvant use of midodrine to IVV in the ICU. The outcomes of interest were ICU length of stay (LOS), hospital LOS, mortality, IVV reinstitution, ICU readmission, and bradycardia. Estimates were pooled using the random-effects model. We reported effect sizes as standardized mean difference (SMD) for continuous outcomes and risk ratios (RRs) for other outcomes with a 95% confidence interval (CI). Results . A total of 6 studies were found that met inclusion criteria and had sufficient data for our quantitative analysis (1 randomized controlled trial and 5 retrospective studies). A total of 2, 857 patients were included: 600 in the midodrine group and 2, 257 patients in the control group. Midodrine use was not associated with a significant difference in ICU LOS (SMD 0.16 days; 95% CI −0.23 to 0.55), hospital LOS (SMD 0.03 days; 95% CI −0.33 to 0.0.39), mortality (RR 0.87; 95% CI 0.52 to 1.46), IVV reinstitution (RR 0.47; 95% CI 0.17 to 1.3), or ICU readmission (RR 1.03; 95% CI 0.71 to 1.49) when compared to using only IVV. However, there were higher trends of bradycardia with midodrine use that did not reach significance (RR 7.64; 95% CI 0.23 to 256.42). Conclusion . This meta-analysis suggests that midodrine was not associated with a significant decrease in ICU LOS, hospital LOS, mortality, or ICU readmissions.